Impact of imposed stroke rate on repeated sprint swimming ability and perceptual cognitive load: effect of expertise and deficiency - Leprêtre, P.; Maruitte, T.; Guimard, A.; Regaieg, M. A.; Letocart, A.; Guignard, B.; Seifert, L. (XIVth International Symposium on Biomechanics and Medicine in Swimming Proceedings, 2023)
INTRODUCTION High level of motor flexibility, illustrated by stroke rate (SR) changes during competitive event, may explain the swimming performance (Seifert et al. 2014). The study aimed to determine whether the SR imposition could impact performance and perceptual cognitive load (PCL) in higher and lower proficiency swimmers and para-swimmers. METHOD 26 swimmers and 9 para-swimmers (20.4±4.3y, 177.6±9.1cm, 68.1±8.8kg) performed 50m sprint in their speciality at their freely-chosen SR (FC) and at the imposed mean SR, based on the averaged FC. Then all the subjects randomly swam 4 ´ 50m at SR-6, SR-3, SR+3 and SR+6, separated by 7-min of passive recovery. SR was imposed by a Tempo trainer (Finis Inc, Livermore, USA) (Altavilla et al. 2018). Perceptual cognitive load was measured by visual analogic scale, 3-min after each 50m. RESULTS All the swimmers were significantly faster during FC compared other conditions (p 0.008). Performance during mean SR was higher than SR-6 (p 0.020). SR+3 and SR+6 conditions induced a significant higher perceptual cognitive load value compared to FC trial (p 0.001). Logistic regression showed that the ability to repeat the same level of swimming performance (i.e., < 5% changes with FC condition), was related to proficiency (p 0.002), the ability to swim quickly at the lowest (SR-6) and highest (SR+6) imposed SR (p 0.022), disability (p 0.023) and swimming speed (p 0.038). No relation was found between the repeated sprint ability and the perceptual cognitive load (p 0.671). DISCUSSON Higher proficiency able-bodied swimmers seem to be able to use a large SR range to perform.